The defense lawyer ebook The barry slotnick story. - Patterson, James (2021)
From a master of true crime comes the story of the criminal lawyer who represented everybody from Manuel Noriega to John Gotti to Bernie Goetz—and won every single case. Known for his sharp mind, sharp suits, and bold courtroom strategies, Bronx-native Barry Slotnick is known as the best criminal lawyer in the US.   He calls himself “Liberty’s Last Champion.”   Slotnick mediates Bette Midler’s bathhouse contract and represents John Gotti, “The Dapper Don.” He defends “Subway Shooter” Bernie Goetz and negotiates future First Lady Melania Trump’s pre-nup.   His unparalleled legal brilliance defines a profession, a city—and an era.